Farmers' Response Towards Technological Interventions Under Assessment and Refinement - R. K. Singh , S. K. Dubey , R. P. Singh Ratan and D. Das Gupta, (Indian Journal of Extension Education, 2013)
Farmers' responses towards technology assessment and refinment were sutdied in five villages of Karge panchayat ofMandar block in Ranchi District of Jharkhand. Results revealed that all the intervened technologies assessed by thefarmers' were agro-climatically more suitable, more profitable and more compatible, which contributed to their overallappropriateness in comparison to the corresponding farmers' practices. Overall reaction of the respondents on intervenedtechnologies was found to be positive in terms of selected attributes i.e. socio-cultural compatibility, compatibility withexisting farming system components, divisibility of technology, simplicity, compatibility with internal resources of thehouseholds, element of risk involved and visibility except their easy availability in the local markets. Majority of thefarmers' felt difficulties in accepting the recommended technologies as such in respect of most of the intervenedtechnologies and preferred the refined technologies which were suitable in their agro-ecological situation and socioeconomic condition.